Assessing Heavy Metal Contamination in Stream Sediment and Water in Idofian, Kwara State: A Geochemical Perspective - Emmanuel Bamikole; Ajoke Omorinoye, Omolayo; Sijuade Bamigboye, Olufemi; bdulhameed Kayode, Oniyangi (Journal of Sustainable Natural Resources, 2024)
Environmental geochemistry examines the presence, dispersion, and movement of elements on the Earth’s surface. This research explores the environmental geochemistry of the Idofian area in Kwara State, Nigeria, with a particular emphasis on water and stream sediments. The heavy metals were ascertained using X-ray diffraction (XRD) and atomic absorption spectrometer (AAS). The study revealed the presence of marble, diorite, gneiss, pegmatite and amphibolite in the Idofian area. Furthermore, the XRD analysis provided information about the mineral composition including quartz, micas, lepidolite, laumontite, orthoclase, plagioclase, dolomite and anthophyllite. The findings revealed the absence of sediment contamination, while highlighting substantial contamination in the study area’s water. This contamination, attributed to a combination of geogenic and anthropogenic factors, underscores the crucial necessity for implementing sustainable management practices in the region.